CellMAP: an open-source software tool to batch-process cell topography and stiffness maps collected with an atomic force microscope - Antoine Allard; Maxime Liboz; Raphaël Crépin; Sid Labdi; Olek Maciejak; Michel Malo; Clément Campillo; Guillaume Lamour (BMC Bioinformatics)
Abstract Atomic force microscopy (AFM) is the gold-standard technique to simultaneously map the morphology and viscoelastic properties of living cells. Although existing software tools, both open-source and from AFM manufacturers, can analyze cells individually, there is a growing need for fast and accessible codes to compile data from multiple cells into a single dataset. To address this, we present CellMAP, a user-friendly software tool that streamlines the batch-processing of AFM-derived topography and stiffness maps of living cells. Our analysis pipeline includes but is not limited to: flattening of the underlying substrate surface, filtering of outlier values, measurement of the cell surface and volume, and measurement of height and stiffness distributions. CellMAP can also generate a composite cell that reflects the height and stiffness properties of an entire cell population.